Copper-Catalyzed One-Pot Synthesis of Chalcogen-Benzothiazoles/Imidazo[1,2-a]pyridines with Sulfur/Selenium Powder and Aryl Boronic Acids - Guo, Tao; Wei, Xu-Ning; Zhu, Ying-Li; Chen, Huan; Han, Shu-Lei; Ma, Yong-Cheng (Synlett, 2018)
An efficient and convenient copper-catalyzed oxidative chalcogenation of benzothiazoles and imidazo[1,2-a]pyridines with sulfur/selenium powder and aryl boronic acids was developed. This procedure allows access to a wide range of structurally diverse arylchalcogen-substituted benzothiazoles/imidazo[1,2-a]pyridines in good yields and with good functional group tolerance. A biological evaluation revealed that some of the obtained products exhibited in vitro antiproliferative activities on human-derived lung, stomach, esophageal, and breast cancer cell lines.
Keywords: benzothiazoles; imidazoheterocycles; chalcogenation; C–H activation; copper